Hubungan Antara Screentime dengan Kejadian Kelelahan Mata dan Nyeri Kepala pada Siswa SMAN 3 Sumedang - Renanda Futri Dewi; Nunung Siti Sukaesih; Imam Tri Sutrisno (Jurnal Keperawatan Galuh, 2026)
The increasing intensity of digital device use in adolescents leads to high screen time duration, potentially triggering physical complaints such as eye fatigue and headaches. This study aims to analyze the relationship between screen time duration and the incidence of eye fatigue and headaches in students. This quantitative study with a cross-sectional design involved 279 students of SMA Negeri 3 Sumedang. Data were collected using a structured questionnaire regarding screen time duration and levels of eye fatigue and headaches, then analyzed using the Spearman-rho correlation test. The average screen time duration of students reached 8.5 hours per day, and as many as 50.5% of respondents experienced eye fatigue. The results of statistical tests showed a significant positive relationship between screen time duration and the incidence of eye fatigue (p = 0.038; r = 0.124). These findings indicate that high screen time duration is significantly associated with eye fatigue in students. Clinically, the results of this study emphasize the importance of education about limiting screen time and implementing regular eye breaks as a promotive and preventive effort in maintaining adolescent eye health.